An Unusual Case of Peripheral Nerve Vasculitis - S. Wang; Arsany A.; D. Feinstein; P. Traisak; H. Eid; M. Karpoff (Case Reports in Rheumatology)
Peripheral neuropathy is a common manifestation of systemic vasculitis. The etiology of vasculitic peripheral neuropathy is generally classified into two groups: systemic and nonsystemic. In systemic vasculitic neuropathy (SVN), neuropathy is a consequence of a systemic disease, most commonly involving medium and small vessels throughout the body. There are three main clinical presentations: multifocal neuropathy, distal symmetric polyneuropathy, and overlapping multifocal neuropathy. Specifically, distal symmetric polyneuropathy affects multiple somatic nerves diffusely in a symmetric and length-dependent pattern (also known as the classic stocking-glove pattern). This case represents an atypical presentation of SVN, presenting with widespread symmetric polyneuropathy.A 73-year-old woman presented with distal acute on chronic bilateral upper and lower extremity weakness, sensory changes, and widespread pain. Symptoms started about three months prior and gradually worsened with progressive difficulty with ambulation and required assistive devices. Elevated ESR is at 70 mm/hour, CRP at 25.66 mg/dL, elevated c-ANCA titers at 1 : 320 and PR3 at 5.0 AI, and elevated creatine kinase (CK) at 500–600 U/L. A muscle biopsy of the left vastus showed neurogenic atrophy without myositis. Initial improvement was with oral prednisone, but was stopped on discharge. Many purpuric and petechial lesions were developed on distal legs/feet and right fourth digit distal gangrene. EMG showed distal, symmetric, and axonal polyneuropathy affecting the upper and lower extremities and acute denervation in more distal muscles. The patient received pulse dose steroids and two doses of rituximab induction therapy and was discharged with an oral steroid taper. The patient’s symptoms started as distal symmetric neuropathy at the onset and progressively worsened over the course of 3 months. Neuropathy, both on the exam and on EMG, seemed to have developed more rapidly than expected, regardless of its distribution. The EMG showed severe peripheral nerve damage and denervation, which is unusual for ANCA-associated systemic vasculitis.